Pre-diagnostic and non-advanced systemic mastocytosis without cutaneous involvement have an increased risk of anaphylaxis - Sangalli, Andrea; Pravettoni, Valerio; Sciumè, Mariarita; Consonni, Dario; Sartorio, Silvio; Montano, Nicola; Rivolta, Federica (Frontiers in Allergy, 2025)
BackgroundPatients with mastocytosis have a higher risk of anaphylactic reactions. This study aims to assess the prevalence and risk factors of anaphylaxis among patients diagnosed with Systemic Mastocytosis (SM), including pre-diagnostic Systemic Mastocytosis (pre-SM), a subgroup of patients often overlooked in current classifications.MethodsA retrospective monocentric study was conducted at Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico in Milan, Italy. Patients aged ≥18 years diagnosed with SM or pre-SM between January 2009 and May 2025 were included. Demographic, clinical and laboratory data were analyzed using chi-squared test or Wilcoxon-Mann–Whitney and Kruskal–Wallis testsResultsAt the time of diagnosis, out of 162 patients (53% women), 29 (18%) experienced at least one episode of anaphylaxis. Hymenoptera venom was the main trigger (51.7%), followed by drugs (27.6%) and idiopathic cases (20.7%). Patients with anaphylaxis had 7% pre-SM, 48% BMM, 28% ISM, 0% SSM, 7% ASM, 10% SM-AHN, (p < 0.001). The prevalence of anaphylaxis in each subtype was as follows: 2/12 (17%) in pre-SM, 14/31 (45%) in BMM, 8/97 (8%) in ISM, 0/5 in SSM, 2/4 (50%) in ASM and 3/13 (23%) in SM-AHN, (p < 0.001). Hymenoptera venom–induced anaphylaxis occurred exclusively in indolent forms (pre-SM, BMM, and ISM) while drug-induced anaphylaxis was observed in both ISM and advanced SM subtypes. Idiopathic anaphylaxis was more evenly distributed across all SM subtypes, (p < 0.001). The presence of cutaneous lesions was associated with a lower risk of anaphylaxis: 10/114 (8.8%) vs. 19/48 (39.6%) without skin involvement (p < 0.001), with a confirmed protective effect in both ISM and pre-SM. Male sex was identified as an additional risk factor, (p = 0.03). A history of Hymenoptera sting was associated with a higher risk of Hymenoptera venom anaphylaxis: 15/113 (13%) vs. no reactions to the first sting in 47 patients, (p = 0.011).ConclusionAnaphylaxis is a relevant issue not only in acknowledged variants of SM, but also in pre-diagnostic forms. Idiopathic anaphylaxis may occur across different subtypes. Hymenoptera venom is the main trigger in indolent forms, whereas drug-induced reactions predominate in ISM and advanced SM, mainly through IgE-independent mechanisms. The risk of anaphylaxis is higher in pre-SM and ISM without cutaneous involvement, particularly in case of Hymenoptera venom sensitization. Our results highlight the need for allergological risk assessment and close monitoring especially in patients without skin lesions or with Hymenoptera venom sensitization.